The Influence of Brand Awareness and Brand Trust on Purchasing Decisions for Oronamin C Products - Bachtiar, Muhammad Daffa; Indriani, Sri; Rupianti, Reni (PT Aksara Indo Rajawali, 2025)
In the context of product marketing, brand awareness and brand trust are key factors that influence consumer purchasing decisions. For this reason, a company needs the right strategy to increase brand awareness and brand trust of the products it offers. This research aims to analyze the influence of brand awareness and brand trust on purchasing decisions, with a focus on Oronamin C products. This type of research is quantitative, with a sample size of 110 individuals who consume Oronamin C products. Data collection in this research uses a questionnaire distributed to respondents using a purposive sampling technique. This data was analyzed using multiple linear regression using SPSS version 24. The results of this research show that the level of brand awareness and brand trust has a positive and significant influence on the decision to purchase Oronamin C products. This research provides insights for academics and companies in the packaged drinks and vitamin drinks industries on how to enhance purchasing decisions for ion-packed beverage products in Indonesia.